2015
DOI: 10.4102/ojvr.v82i1.900
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of <i>Culicoides</i> species, the vectors of arboviruses, at selected trap sites in Zimbabwe

Abstract: A study of the distribution of Culicoides species was conducted by establishing 12 light trap sites over five rainy seasons between 1998 and 2003 covering all the geo-climatic natural regions of Zimbabwe. In total, 279 919 specimens of Culicoides were trapped over a total of 163 trapping nights. The highest median counts of Culicoides per trapping night were recorded in natural region III, which has climatic conditions conducive to the successful development of the larvae. Culicoides imicola, the major vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The sentinel herds were situated in the Highveld of Zimbabwe, which is characterised by high rainfall and temperature that favour the abundance of the Culicoides vector(s). The sero-incidence of AHSV and EEV antibodies in sentinel herds at some of the farms closely matched the number of Culicoides vectors trapped per night at these farms, as reported in previous studies by Gordon ( 2010 ) and Gordon et al ( 2015 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The sentinel herds were situated in the Highveld of Zimbabwe, which is characterised by high rainfall and temperature that favour the abundance of the Culicoides vector(s). The sero-incidence of AHSV and EEV antibodies in sentinel herds at some of the farms closely matched the number of Culicoides vectors trapped per night at these farms, as reported in previous studies by Gordon ( 2010 ) and Gordon et al ( 2015 ).…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that the incidence of these diseases will have the same seasonality as the vector species. Gordon et al ( 2015 ) found the greatest diversity and highest median counts of Culicoides to be in the central Highveld region of Zimbabwe where climatic and geophysical conditions favoured optimal breeding and larval development. Although the vector competence of most Culicoides species in Zimbabwe has not been studied in detail, Gordon et al ( 2015 ) isolated Orbiviruses from Culicoides imicola which included EEV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The climate in these regions favours Culicoides vectors. Farms were selected on the basis of age (> 1 year), herd size (> 8) and owners’ cooperation and were typical of the Zimbabwean Highveld, having similar soil, vegetation and agricultural practices (Gordon 2010 ; Gordon et al 2015 ; Musuka 1999 ). The cattle and sheep on these premises had no history of prophylactic immunisation against BTV or EHDV, which meant that subsequently detected antibodies against these viruses would have been derived from natural challenge.…”
Section: Methodsmentioning
confidence: 99%
“…No clinical cases of EHD have been reported in Zimbabwe to date and there are no published data on the sero-prevalence or sero-incidence of antibodies against EHDV in ruminants in the country (Gordon 2010 ; Musuka 1999 ). Although one study has isolated BTV from Culicoides imicola and Culicoides magnus (Gordon et al 2015 ), the vector competence of other Culicoides species in Zimbabwe has not been documented and needs further investigation.…”
Section: Introductionmentioning
confidence: 99%